Study on characteristics of the cavitation bubble dynamics of lithium bromide aqueous solution with ultrasonic interaction. (December 2021) - Hou, Zhaoning; Wang, Lin; Yan, Xiaona; Wang, Zhanwei; An, Libei
Abstract: Solar absorption refrigeration (SAR) system occupies large building energy consumption, due to its low generation efficiency. Depending on the mechanism of enhanced disturbance and convection, this paper proposes the application of ultrasound heat-transfer enhancement technology in the boiling heat-transfer of LiBr/H2 O solution in the generator to enhance system performance. At present, there are few theoretical and experimental studies about the ultrasound on heat-transfer enhancement in the salt solution, especially in the field of multi-frequency ultrasound (MFU) bubble dynamics. The motion of a cavitation bubble has significant impact on the disturbance and convection in the solution. Thus, the mathematical models of cavitation bubble dynamics (CBD) are constructed to evaluate the solution cavitation characteristics, the CBD on boiling heat-transfer in the generator is investigated, and the effect of the number of ultrasonic vibrators (UVs) on the cavitation bubble radius (CBR) is investigated to explore the cavitation characteristics of MFU. The results indicate that: the low-frequency ultrasound on the heat-transfer in vacuum generator is more obviously effect, due to enhance solution mixing around the heating surface; the maximum CBR could be increased by increasing the number of UVs, while the maximum CBR is increased by no more than 1% at the number of UVs of 24–25 and the total sound intensity of 1 W/cm 2, respectively; the solution in vacuum generator could produce transient-cavitation with MFU. This study, not only reaffirms the benefit of using the MFU for generator of SAR system, but also provides some rules of the cavitation characteristics of MFU. Highlights: Ultrasound on heat-transfer enhancement in LiBr/H2 O solution for generating process is presented. Influence of ultrasonic parameters is investigated. Effect of the number of ultrasonic vibrators on the cavitation bubble is analyzed. The cavitation bubble dynamics between LiBr/H2 O solution and degassed water are compared.